Scooby-Doo! and the curse of the 13th ghost [videorecording (DVD)] : original movie - Hamilton, Cecilia Aranovich (Warner Bros. Entertainment, 2019)
The Scooby-Doo gang comes to the aid of their old friend Vincent Van Ghoul to capture the thirteenth ghost and break a curse.